2019
DOI: 10.3847/2041-8213/ab487d
|View full text |Cite
|
Sign up to set email alerts
|

No Snowball on Habitable Tidally Locked Planets with a Dynamic Ocean

Abstract: Terrestrial planets orbiting within the habitable zones of M-stars are likely to become tidally locked in a 1:1 spin:orbit configuration and are prime targets for future characterization efforts. An issue of importance for the potential habitability of terrestrial planets is whether they could experience snowball events (periods of global glaciation). Previous work using an intermediate complexity atmospheric Global Climate Model (GCM) with no ocean heat transport suggested that tidally locked planets would sm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 53 publications
(65 reference statements)
3
45
0
Order By: Relevance
“…The mixing ratios of the species are constant over height. We consider pressures leading to surface temperatures between 220 K (approximated limit of open water with ocean heat transport in climates of tidally locked exoplanets around M dwarf stars, see Hu & Yang 2014;Checlair et al 2017Checlair et al , 2019 and 395 K (see Clarke 2004;McKay 2014). Further we limit our Notes.…”
Section: Climate-only Runsmentioning
confidence: 99%
“…The mixing ratios of the species are constant over height. We consider pressures leading to surface temperatures between 220 K (approximated limit of open water with ocean heat transport in climates of tidally locked exoplanets around M dwarf stars, see Hu & Yang 2014;Checlair et al 2017Checlair et al , 2019 and 395 K (see Clarke 2004;McKay 2014). Further we limit our Notes.…”
Section: Climate-only Runsmentioning
confidence: 99%
“…M-dwarf stars like TRAPPIST-1 emit a greater fraction of radiation at longer wavelengths compared to the sun, which leads to a reduction in ice-albedo feedback for planets around such stars (Shields et al 2013). The reduction of this ice-albedo feedback leads to the loss of bistability in the climate system, which has been demonstrated using calculations with EBMs and GCMs (Checlair et al 2017(Checlair et al , 2019. Calculations with the tidally-locked configuration of HEXTOR likewise do not show bistability between frozen and ice-free states analogous to the rapidly rotating cases shown in Fig.…”
Section: Geographymentioning
confidence: 80%
“…A similar result was observed by Checlair et al (2017), who observed a small amount of hysteresis using a GCM of intermediate complexity when examining synchronously rotating planets with a cold start versus a warm start. Such hysteresis is likely due to limitations of the GCM, and this hysteresis indeed vanished in subsequent experiments by Checlair et al (2019) with a more complex GCM that included a dynamic ocean. Similarly, this hysteresis in HEXTOR for synchronously rotating planets is likely a model artefact, rather than a physical result, due to the limitations of the diffusive energy transport parameterization.…”
Section: Geographymentioning
confidence: 90%
“…A similar result was observed by Checlair et al (2017), who observed a small amount of hysteresis using a GCM of intermediate complexity when examining synchronously rotating planets with a cold start versus a warm start. Such hysteresis is likely due to limitations of the GCM, and this hysteresis indeed vanished in subsequent experiments by Checlair et al (2019) with a more complex GCM that included a dynamic ocean. Similarly, this hysteresis in HEXTOR for synchronously rotating planets is likely a model artifact, rather than a physical result, due to the limitations of the parameterization of diffusive energy transport.…”
Section: Synchronously Rotating Terrestrial Planetsmentioning
confidence: 90%